Bactericidal Action of Streptomycin and Comparison with Spectinomycin in Heterozygotes of Escherichia coli - Sparling, P. Frederick (1972)
Str(s)/str(r) heterozygotes of Escherichia coli K-12 are shown to be sensitive to the lethal as well as the inhibitory action of streptomycin. The rate of killing was lower in heterozygotes than in sensitive homozygotes, and among heterozygotes it was lower in those with a higher proportion of resistant ribosomes. These strains also differed, in a parallel manner, in the kinetics of inhibition of growth and protein synthesis by streptomycin. Similar results were obtained with spectinomycin and corresponding merodiploid strains. Since spectinomycin is purely bacteriostatic and stabilizes polysomes, it must block resistant ribosomes behind inhibited sensitive ribosomes; hence, these results are consistent with an initial similar polysomal blockade by streptomycin. However, since streptomycin causes gradual polysome breakdown, its dominant lethal action must involve some mechanism other than a permanent polysomal blockade.